2018
DOI: 10.1136/bmjgh-2017-000682
|View full text |Cite
|
Sign up to set email alerts
|

A long way to go: a systematic review to assess the utilisation of sexual and reproductive health services during humanitarian crises

Abstract: IntroductionWomen and girls are affected significantly in both sudden and slow-onset emergencies, and face multiple sexual and reproductive health (SRH) challenges in humanitarian crises contexts. There are an estimated 26 million women and girls of reproductive age living in humanitarian crises settings, all of whom need access to SRH information and services. This systematic review aimed to assess the utilisation of services of SRH interventions from the onset of emergencies in low- and middle-income countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
111
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(129 citation statements)
references
References 30 publications
3
111
0
2
Order By: Relevance
“…In addition, there has been potential and actualization of continuing sexual abuse of both women and children within the refugee camps. Additionally, there continues to be limited reproductive health care in the camps (Singh et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there has been potential and actualization of continuing sexual abuse of both women and children within the refugee camps. Additionally, there continues to be limited reproductive health care in the camps (Singh et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…A recent review of uptake of sexual and reproductive services in humanitarian crises identified gaps in knowledge in several key areas. 2 For example, scant research has examined prevention of vertical HIV transmission, prevention and treatment of sexually transmitted infections, abortion and post-abortion care, or clinical management of rape. 2 The Inter-Agency Working Group on Reproductive Health in Crises 12 is a coalition of 20 steering committee member agencies.…”
Section: The Potential For Self Care In Humanitarian Crisesmentioning
confidence: 99%
“…1 Humanitarian crises disrupt communities to such an extent that they require national or international resources and help. 1 2 Forcibly displaced people include those who have left their home but have not crossed an international border (internally displaced people); those who have left their country because of persecution, war, and violence (refugees); and people who have applied for sanctuary in another country (asylum seekers). 1…”
mentioning
confidence: 99%
See 2 more Smart Citations